Defining Bicircular Matroids in Monadic Logic. (29th March 2021) - Funk, Daryl; Mayhew, Dillon; Newman, Mike
Abstract: We conjecture that the class of frame matroids can be characterized by a sentence in the monadic second-order logic of matroids, and we prove that there is such a characterization for the class of bicircular matroids. The proof does not depend on an excluded-minor characterization.